2005
DOI: 10.1007/s10295-005-0050-7
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis and comparison of Clostridium acetobutylicum ATCC 824 and Spo0A strain variants

Abstract: The proteomic profiles of several Clostridium acetobutylicum strains were compared by two-dimensional gel electrophoresis and mass spectroscopy. The proteomic profile of C. acetobutylicum wild type strain ATCC 824 with and without a commonly used control plasmid and with a spo0A overexpression plasmid pMSPOA was compared. A total of 2,081 protein spots were analyzed; 23 proteins were chosen to be identified of which 18 were unique and 5 were proteins located in more than one location. The proteins identified w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
40
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 47 publications
6
40
0
Order By: Relevance
“…Phosphate acetyltransferase (CAC1742) involved in the catalysis of acetyl CoA to acetyl phosphate leading to the production of acetate [10] and acetoacetate decarboxylase (CAP0165) [genes involved in the solvent formation resides on the plasmid and hence the prefix CAP] [19], which is essential for the solvent production that catalyzes the decarboxylation of acetoacetate to acetone [23], were found to be significantly lower in expression from the stationary phase in comparison to the exponential growth. In contrast, proteomic analysis of C. acetobutylicum using glucose reported that acetoacetate decarboxylase is upregulated from exponential to stationary phase [31]. These findings were consistent with the protein-abundance analysis, which showed that (abrB) stationary/sporulation gene expression regulator protein (CAC0310) as the most abundant in stationary phase of xylose utilized ABE fermentation and Spo0A protein as the most abundant using glucose [31].…”
Section: Differentially Expressed Proteinssupporting
confidence: 72%
See 3 more Smart Citations
“…Phosphate acetyltransferase (CAC1742) involved in the catalysis of acetyl CoA to acetyl phosphate leading to the production of acetate [10] and acetoacetate decarboxylase (CAP0165) [genes involved in the solvent formation resides on the plasmid and hence the prefix CAP] [19], which is essential for the solvent production that catalyzes the decarboxylation of acetoacetate to acetone [23], were found to be significantly lower in expression from the stationary phase in comparison to the exponential growth. In contrast, proteomic analysis of C. acetobutylicum using glucose reported that acetoacetate decarboxylase is upregulated from exponential to stationary phase [31]. These findings were consistent with the protein-abundance analysis, which showed that (abrB) stationary/sporulation gene expression regulator protein (CAC0310) as the most abundant in stationary phase of xylose utilized ABE fermentation and Spo0A protein as the most abundant using glucose [31].…”
Section: Differentially Expressed Proteinssupporting
confidence: 72%
“…Very few proteomic studies have been conducted in C. acetobutylicum using one-and/or two-dimensional gel electrophoresis-mass spectrometry (1D/2D-GE-MS) technique. Besides, most of them were from C. acetobutylicum grown on glucose substrate and focused specifically on proteins involved in acidogenic and solventogenic pathways [28,31]. A total of 564 proteins identified from the exponential growth of glucose utilized C. acetobutylicum DSM1731 strain were used to publish the proteome reference map [17].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DNA microarrays have shown signiWcant diVerences in the expression of at least 123 genes between wild type and strain 824(pMspo0A), as well as signiWcant transcriptional diVerences between the acidogenic and solventogenic phases in wild type C. acetobutylicum and the asolventogenic mutant strain, M5 [4,5]. 2D gel analysis of the proteome of wild type, SKO1 and 824(pMspo0A) revealed signiWcantly diVerent levels of heat shock proteins, metabolic regulators and translational proteins between strains [6]. Such surveys are useful in allowing us to gage the complexity of the lifecycle of C. acetobutylicum.…”
Section: Introductionmentioning
confidence: 99%